2021
DOI: 10.1155/2021/7006541
|View full text |Cite|
|
Sign up to set email alerts
|

[Retracted] Analysis of Body Behavior Characteristics after Sports Training Based on Convolution Neural Network

Abstract: The use of artificial intelligence technology to analyze human behavior is one of the key research topics in the world. In order to detect and analyze the characteristics of human body behavior after training, a detection model combined with a convolutional neural network (CNN) is proposed. Firstly, the human skeleton suggestion model is established to analyze the driving mode of the human body in motion. Secondly, the number of layers and neurons in CNN are set according to the skeleton feature map. Then, the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 25 publications
0
3
0
Order By: Relevance
“…Basic movements for children include walking, running, jumping, throwing, balancing, drilling, and climbing; basic gymnastics includes changing formations and queues. This experiment is also carried out around the basic movements, Figure 5 is a schematic diagram of children's sports training: Basic movements have a developmental process [27]. The so-called development refers to the change of things from small to large, from simple to complex, and from low-level to high-level.…”
Section: Children's Sportsmentioning
confidence: 99%
“…Basic movements for children include walking, running, jumping, throwing, balancing, drilling, and climbing; basic gymnastics includes changing formations and queues. This experiment is also carried out around the basic movements, Figure 5 is a schematic diagram of children's sports training: Basic movements have a developmental process [27]. The so-called development refers to the change of things from small to large, from simple to complex, and from low-level to high-level.…”
Section: Children's Sportsmentioning
confidence: 99%
“…Tis article has been retracted by Hindawi following an investigation undertaken by the publisher [1]. Tis investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process:…”
mentioning
confidence: 99%
“…This article has been retracted by Hindawi following an investigation undertaken by the publisher [ 1 ]. This investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process: Discrepancies in scope Discrepancies in the description of the research reported Discrepancies between the availability of data and the research described Inappropriate citations Incoherent, meaningless and/or irrelevant content included in the article Peer-review manipulation …”
mentioning
confidence: 99%